Large-scale, prospective observational study of regorafenib in Japanese patients with advanced gastrointestinal stromal tumors in a real-world clinical setting - Komatsu, Yoshito; Muro, Kei; Chosa, Masayuki; Hirano, Kazufumi; Sunaya, Toshiyuki; Ayukawa, Koichi; Hattori, Kana; Nishida, Toshirou (Frontiers in Oncology, 2024)
Background Regorafenib improves overall survival (OS) of patients with advanced progressive gastrointestinal stromal tumors (GISTs) after standard chemotherapy in phase III trials in the 3rd-line setting. This large-scale, prospective observational study evaluated the safety and effectiveness of regorafenib in Japanese patients with GIST in a real-world clinical setting. Methods Patients with GIST received oral regorafenib at a maximum daily dose of 160 mg for weeks 1–3 of each 4-week cycle (dose could be modified at investigator’s discretion). The primary objective was to assess safety, particularly significant adverse drug reactions (ADRs), as well as the frequency of occurrence of ADRs, hand and foot syndrome (HFS), discontinuation of treatment due to disease progression and adverse events. A Cox proportional hazards model was used to evaluate associations between OS or time to treatment failure (TTF) and baseline characteristics or HFS. Results Between August 2013 and March 2021, 143 evaluable patients were enrolled. ADRs occurred in 90.2% of patients and led to treatment discontinuation in 28.3%. The most frequent ADRs were HFS, hypertension, and liver injury. The overall response rate was 11.3% and disease control rate 56.5% (RECIST) based on investigators’ assessments. Median OS was 17.4 months (95% CI 14.24–23.68). Median TTF was 5.3 (95% CI 4.0–6.5) months. Improved OS and TTF responses occurred in patients with an Eastern Cooperative Oncology Group performance status (ECOG-PS) of 0 or 1. Conclusion The outcomes in this real-world study were consistent with those seen in clinical trials. No new safety concerns were identified. Clinical trial registration https://clinicaltrials.gov, identifier NCT01933958.